Gene expression patterns in primary neuronal clusters of the Drosophila embryonic brain - Sprecher, Simon G. (2007)
The brain of Drosophila is formed by approximately 100 lineages, each lineage being derived from a stem cell-like neuroblast that segregates from the procephalic neurectoderm of the early embryo. A neuroblast map has been established in great detail for the early embryo, and a suite of molecular markers has been defined for all neuroblasts included in this map (Urbach and Technau, 2003a). However, the expression of these markers was not followed into later embryonic or larval stages, mainly due to the fact that anatomical landmarks to which expression patterns could be related had not been defined. Such markers, in the form of stereotyped clusters of neurons whose axons project along cohesive bundles (“primary axon bundles” or “PABs”) are now available (Younossi-Hartenstein et al., 2006). In the present study we have mapped the expression of molecular markers in relationship to primary neuronal clusters and their PABs. The markers we analyzed include many of the genes involved in patterning of the brain along the anteroposterior axis (cephalic gap genes, segment polarity genes) and dorso-ventral axis (columnar patterning genes), as well as genes expressed in the dorsal protocerebrum and visual system (early eye genes). Our analysis represents an important step along the way to identify neuronal lineages of the mature brain with genes expressed in the early embryo in discrete neuroblasts. Furthermore, the analysis helped us to reconstruct the morphogenetic movements that transform the two-dimensional neuroblast layer of the early embryo into the three-dimensional larval brain and provides the basis for deeper understanding of how the embryonic brain develops.